The Fate of SWCNTs in Mouse Peritoneal Macrophages: Exocytosis, Biodegradation, and Sustainable Retention - Dong, Ping-Xuan; Song, Xinfeng; Wu, Jiwei; Cui, Shuqin; Wang, Guizhi; Zhang, Lianying; Sun, Hanwen (Frontiers in Bioengineering and Biotechnology, 2020)
The understanding of toxicological and pharmacological profiles of nanomaterials is an important step for the development and clinical application of nanomedicines. Carbon nanotubes (CNTs) have been extensively explored as a nanomedicine agent in pharmaceutical/biomedical applications, such as drug delivery, bioimaging, and tissue engineering. The biological durability of CNTs could affect the function of CNTs-based nanomedicines as well as their toxicity in cells and tissues. Therefore, it is crucial to assess the fate of nanomedicine in phagocytes. Herein, we investigated the candidate fate of acid-oxidized single-walled carbon nanotubes (SWNCTs) in non-activated primary mouse peritoneal macrophages (PMQ). The sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) results showed that the intracellular SWCNTs continued growing from 4 to 36 h in PMQ. After replacing the exposure medium, we found the exosome induced by SWCNTs on the surface of macrophages according to scanning electron microscope (SEM) observation. The near-infrared (NIR) absorption increase of the supernatant samples after post-exposure indicates that SWCNTs exocytosis occurred in PMQ. The decreasing intracellular SWCNTs amount suggested the incomplete biodegradation in PMQ, which was confirmed by Raman spectroscopy and transmission electron microscopy (TEM). The combined data reveal that SWCNTs could be retained for more than 60 h in macrophages. Then sustainable retention of SWCNTs in primary macrophages was coexist with exocytosis and biodegradation. The findings of this work will shed light on the bioimaging, diagnosis and other biomedical applications of CNTs-based nanomedicines.